Different Cytokine and Chemokine Expression Patterns in Malignant Compared to Those in Nonmalignant Renal Cells. (9th July 2017) - Gelbrich, Nadine; Ahrend, Hannes; Kaul, Anne; Brandenburg, Lars-Ove; Zimmermann, Uwe; Mustea, Alexander; Burchardt, Martin; Gümbel, Denis; Stope, Matthias B.
Abstract : Objective . Cytokines and chemokines are widely involved in cancer cell progression and thus represent promising candidate factors for new biomarkers. Methods . Four renal cell cancer (RCC) cell lines (Caki-1, 786-O, RCC4, and A498) and a nonmalignant renal cell line (RC-124) were examined with respect to their proliferation. The cytokine and chemokine expression pattern was examined by a DNA array (Human Cytokines & Chemokines RT 2 Profiler PCR Array; Qiagen, Hilden, Germany), and expression profiles were compared. Results . Caki-1 and 786-O cells exhibited significantly increased proliferation rates, whereas RCC4 and A498 cells demonstrated attenuated proliferation, compared to nonmalignant RC-124 cells. Expression analysis revealed 52 cytokines and chemokines primarily involved in proliferation and inflammation and differentially expressed not only in malignant and nonmalignant renal cells but also in the four RCC cell lines. Conclusion . This is the first study examining the expression of 84 cytokines and chemokines in four RCC cell lines compared to that in a nonmalignant renal cell line. VEGFA, NODAL, and BMP6 correlated with RCC cell line proliferation and, thus, may represent putative clinical biomarkers for RCC progression as well as for RCC diagnosis and prognosis.